Bitterfrost - Gruley, Bryan (Severn House Publishing, Ltd, 2025)
Thirteen years ago, former ice hockey star Jimmy Baker quit the game after almost killing an opponent. Now, as the Zamboni driver for the amateur team in his hometown of Bitterfrost, Michigan, he's living his penance. Until the morning he awakens to the smell of blood . . .Jimmy soon finds himself arrested for a brutal double murder. The kicker? He has no memory of the night in question. And as the evidence racks up against him, Jimmy's case is skating on thin ice. Could he have committed such a gruesome crime? As his defence attorney Devyn Payne and prosecuting detective Garth Klimmek race to uncover the truth, time is running out for Jimmy. Because all he can really be sure of is that he is capable of taking a life. The question is, in his blacked-out state, did he take two?